2016
DOI: 10.1111/resp.12897
|View full text |Cite
|
Sign up to set email alerts
|

Contractile capability of the diaphragm assessed by ultrasonography predicts nocturnal oxygen saturation in COPD

Abstract: This study suggested a close relationship between the NSpO and the contractile capability of the diaphragm assessed by ultrasonography in COPD. The %ΔTdi combined with PaO might predict NSpO in COPD patients with mild or no daytime hypoxaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…8,9 Diaphragmatic thickness fraction measurements have been reported to be useful in determination of lung hyperinflation in subjects with COPD. 10,11 Ultrasoundbased diaphragmatic thickness fraction measurements have been reported to be useful in determination of lung hyperinflation in subjects with COPD. 10,11 In addition, diaphragmatic thickness fraction has been successfully used for predicting the outcome of weaning and extubation in subjects admitted to the ICU as well as in determining the respiratory effort and the contractile activity of the diaphragm.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 Diaphragmatic thickness fraction measurements have been reported to be useful in determination of lung hyperinflation in subjects with COPD. 10,11 Ultrasoundbased diaphragmatic thickness fraction measurements have been reported to be useful in determination of lung hyperinflation in subjects with COPD. 10,11 In addition, diaphragmatic thickness fraction has been successfully used for predicting the outcome of weaning and extubation in subjects admitted to the ICU as well as in determining the respiratory effort and the contractile activity of the diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Ultrasoundbased diaphragmatic thickness fraction measurements have been reported to be useful in determination of lung hyperinflation in subjects with COPD. 10,11 In addition, diaphragmatic thickness fraction has been successfully used for predicting the outcome of weaning and extubation in subjects admitted to the ICU as well as in determining the respiratory effort and the contractile activity of the diaphragm. 9,[12][13][14][15] Therefore, it may be a potential tool for the assessment of disease status and outcomes in patients with COPD.…”
Section: Introductionmentioning
confidence: 99%
“…used non‐invasive bedside ultrasound during COPD exacerbations to detect diagrammatic dysfunction (DD) that was related to failure of non‐invasive ventilation (NIV) and hospital mortality. Similarly, Okura et al . found that even in non‐hypercapnic, stable COPD patients, DD was related to severity of nocturnal O 2 desaturations, so these patients may be at risk to develop frank ventilatory failure.…”
Section: Copdmentioning
confidence: 93%
“…Antenora et al 37 used non-invasive bedside ultrasound during COPD exacerbations to detect diagrammatic dysfunction (DD) that was related to failure of non-invasive ventilation (NIV) and hospital mortality. Similarly, Okura et al 38 found that even in non-hypercapnic, stable COPD patients, DD was related to severity of nocturnal O 2 desaturations, so these patients may be at risk to develop frank ventilatory failure. In their editorial, Lopez-Campos et al 39 reviewed recent advances in instituting high-pressure nocturnal NIV during stable phase COPD, and described the mechanisms which might account for its beneficial effects.…”
Section: Non-pharmacological Managementmentioning
confidence: 93%
See 1 more Smart Citation